Salmonella pelvic osteomyelitis in an immunocompetent child. (12th May 2011) - Canessa, Clementina; Trapani, Sandra; Campanacci, Domenico; Chiappini, Elena; Maglione, Mariangela; Resti, Massimo
Abstract : A case of Salmonella enteritidis osteomyelitis isolated from the pelvis in a healthy adolescent is reported. Pelvis osteomyelitis is rare in childhood. Moreover, salmonella, typically responsible for bone infection in sickle cell anaemia, is unusually involved in healthy children. Salmonella should be considered among aetiological agents. Antibiotic treatment alone may be successful; however, sometimes, surgical drainage is required.